P‐Glycoprotein (P‐gp)/ABCB1 plays a functional role in extravillous trophoblast (EVT) invasion and is decreased in the pre‐eclamptic placenta. Issue 11 (5th September 2018) - Dunk, Caroline E.; Pappas, Jane J.; Lye, Phetcharawan; Kibschull, Mark; Javam, Mohsen; Bloise, Enrrico; Lye, Stephen J.; Szyf, Moshe; Matthews, Stephen G.
Abstract: Dysregulation of trophoblast differentiation is implicated in the placental pathologies of intrauterine growth restriction and pre‐eclampsia. P‐glycoprotein (P‐gp encoded by ABCB1 ) is an ATP‐binding cassette transporter present in the syncytiotrophoblast layer of the placenta where it acts as a molecular sieve. In this study, we show that P‐gp is also expressed in the proliferating cytotrophoblast (CT), the syncytiotrophoblast (ST) and the extravillous trophoblast (EVT), suggesting our hypothesis of a functional role for P‐gp in placental development. Silencing of ABCB1, via siRNA duplex, results in dramatically reduced invasion and migration, and increased tube formation and fusion in the EVT‐like HTR8/SVneo cell line. In both EVT and CT explant differentiation experiments, silencing of ABCB1 leads to induction of the fusion markers human hCG, ERVW‐1 and GJA1 and terminal differentiation of both trophoblast subtypes. Moreover, P‐gp protein levels are decreased in both the villous and the EVT of severe early‐onset pre‐eclamptic placentas. We conclude that, in addition to its role as a syncytial transporter, P‐gp is a key factor in the maintenance of both CT and EVT lineages and that its decrease in severe pre‐eclampsia may contribute to the syncytial and EVT placental pathologies associated with this disease.